Political participation of women’s rights organisations in democratic practice through legislative advocacy for violence against person prohibition act in Nigeria - Hammawa, Gambo Maimuna (2018)
The evolvement of democracy in Nigeria encouraged political participation in Nigeria. Women right organisations (WROs) have exploited such opportunity to get their voice heard, but their freedom of expression remain repressed. This study explored the political participation of Women right organisations (WROs) in the democratic practice through legislative advocacy of Violence against Persons Prohibition (VAPP) Act in Nigeria. Specifically, the study explored reasons that prompted the participation of WROs and identified WROs activities . It also explored the strategies employed and efforts to overcome challenges in the legislative advocacy. The study utilised a qualitative case study approach and data were retrieved through in-depth interviews, photo elicitation, document reviews and observation methods. The findings of the study revealed among others prevalence in women right abuse, poor legal response and inconformity to international ratified protocols on women’s rights protection as reasons for WROs participation. The result of the study also showed that WROs engaged in information enquiry and dissemination geared towards sensitisation of the general public on the issue of violence against women and by extension influence the government. These were accompanied with strategies such as unified coalition, maximising media opportunities and utilising policy moments employed to influence the policy makers and gain support from the populace. WROs made efforts to overcome challenges through incorporating development partners and collaboration with male champions and National Assembly administrators. However, the outcome of the political participation was unfavourable as WROs were challenged by patriarchal values of the policy makers. The study concluded that WROs were able to utilise their freedom of expression and association to influence the promulgation of the VAPP Act which is a considerable progress in Nigeria’s political and legal development. Yet, they were faced with biases that deterred the VAPP Act from reflecting their complete goal. The findings offered theoretical and policy implications central to understanding the political participation of WROs in legislative advocacy of the VAPP Act in Nigeria.